Medición de resistencias de puestas a tierra en la ciudadela Los Geranios. - Cacay Luzuriaga, Asdrúval Humberto (2013)
A setting system to earth consists on the connection of electric and electronic teams to earth, to avoid that they are damaged in the event of a dangerous transitory current. The objectives of a setting system to earth, reside in to provide security to people and to protect the facilities. To establish a setting system to earth allows having the permanency of a reference potential, when stabilizing the electric tension to earth, under normal conditions of operation. The resistivity of the land is an important and indispensable factor to the moment to constitute a study for a setting to earth. In the mensuration of the resistivity of a land several factors that can affect exist and to vary it, among other has: Nature of the Land, Humidity, Temperature, Salinity, Stratigraphy, Compact and the seasonal Variations. The telurómetro is mainly the instrument that allows to settle down a mensuration of the resistivity of a land or the resistance from a setting to earth, with the use of the method of Wenner. Among the methods to use in the mensuration from the resistance to earth have: method of the two points, method of 62%, method of potential fall, method of the four points, etc. In the resistance mensuration to earth of electrodes, it is necessary to have the knowledge of the factors that you/they can affect the results of the mensurations, among which we have:  The test type.  The type of used apparatus.  The physical place of the test tips. A setting system to earth acquires great importance from the point of view of the security, and any study for an installation it should be strict and to be obligatorily proven, and supported in mensurations.